2017
DOI: 10.1002/1873-3468.12695
|View full text |Cite
|
Sign up to set email alerts
|

NMR studies of the interaction between inner membrane‐associated and periplasmic cytochromes from Geobacter sulfurreducens

Abstract: Geobacter sulfurreducens is a dissimilatory metal-reducing bacterium with notable properties and significance in biotechnological applications. Biochemical studies suggest that the inner membrane-associated diheme cytochrome MacA and the periplasmic triheme cytochrome PpcA from G. sulfurreducens can exchange electrons. In this work, NMR chemical shift perturbation measurements were used to map the interface region and to measure the binding affinity between PpcA and MacA. The results show that MacA binds to Pp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 30 publications
1
15
1
Order By: Relevance
“…Having shown that CbcL and PpcA can exchange electrons, the distinct NMR spectral features of the two cytochromes were then explored to determine the affinity constant of the redox complex. NMR chemical shift perturbation experiments have been used to probe interacting regions between redox proteins, particularly in the oxidized state for which the signal dispersion is considerably larger compared to the reduced form ( Bashir et al, 2011 ; Fonseca et al, 2013 ; Dantas et al, 2017 ; Fernandes et al, 2017 ). This is case of cytochromes CbcL and PpcA whose spectra in the oxidized state are considerably different ( Figure 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Having shown that CbcL and PpcA can exchange electrons, the distinct NMR spectral features of the two cytochromes were then explored to determine the affinity constant of the redox complex. NMR chemical shift perturbation experiments have been used to probe interacting regions between redox proteins, particularly in the oxidized state for which the signal dispersion is considerably larger compared to the reduced form ( Bashir et al, 2011 ; Fonseca et al, 2013 ; Dantas et al, 2017 ; Fernandes et al, 2017 ). This is case of cytochromes CbcL and PpcA whose spectra in the oxidized state are considerably different ( Figure 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Soluble cytochromes may then act as electron shuttles in the periplasm, as described for multiheme cytochromes in Geobacter and Shewanella (40). With the exception of the diheme cytochrome MacA (43), which, in cable bacteria, is predicted as not membrane-associated, no homologs of those well-studied periplasmic cytochromes (e.g., Ppc, Fcc, STC) are present in cable bacteria. Instead, several multiheme cytochromes and 2 single-heme cytochromes with predicted periplasmic or extracytoplasmic localization are conserved among cable bacteria, and some were also expressed in Ca.…”
Section: Cable Bacteria Likely Oxidize Sulfide By Reversal Of the Canmentioning
confidence: 99%
“…In addition to the low-field region of 1D 1 H NMR spectra of cytochromes, the typical and highly dispersed region covered by the signals of the heme substituents of low spin cytochromes in a 2D 1 H, 13 C HSQC spectrum can also be explored to map interacting regions involving these proteins. This strategy was used to monitor the interaction between the inner membrane associated diheme cytochrome MacA and PpcA from G. sulfurreducens (Dantas et al 2017a). 2D 1 H, 13 C HSQC NMR obtained for PpcA in presence of MacA allowed to monitor the most affected PpcA heme substituents and axial ligands (Fig.…”
Section: Selected Biological Applicationsmentioning
confidence: 99%
“…The hemes that experience more chemical shift variations are shown in red. This figure was reproduced with permission from John Wiley and Sons, reference (Dantas et al 2017a) hydrogen peroxide, whereas the other supplies electrons to the redox center and is designated high-potential heme (HP). Due to the molecular weight of MacA the same strategy could not be used to map the interacting regions of MacA in the complex.…”
Section: Selected Biological Applicationsmentioning
confidence: 99%
See 1 more Smart Citation